An English Writing Grammar Error Correction Technology Based on Similarity Algorithm. (20th July 2022) - Li, Qingyu
Abstract : Students are the focus of English writing instruction, which emphasizes their initiative and creativity in the classroom, fosters the development of their self-directed learning and comprehensive language skills, raises their overall English level and mastery ability, and cultivates well-rounded English learners. It is to get yourself out of the dilemma of Chinese English. This study proposes an automatic error correction method for English writing grammar based on a similarity algorithm, which is applied to students during the English writing process. To address the issue of grammatical errors, this study proposes an ontology and grammar rules based on the English writing corpus. Our experimental results demonstrate that our highlighting algorithm can effectively correct grammatical errors in written English, demonstrating the algorithm's efficacy.